2011
DOI: 10.1088/1674-1137/35/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the ν7/2 [503]( f 7/2 ) band in 185 Pt

Abstract: High-spin states in 185Pt have been reinvestigated via the reaction 173Yb(16O, 4n) at a beam energy of 90 MeV. The previously known band based on the ν7/2−[503](f7/2) Nilsson orbital has been extended to higher spin states. Properties of the ν7/2−[503](f7/2) band have been discussed with an emphasis on the evolution of configuration while increasing the spin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In small devices, such as CNT FETs, a single charge trap can have a disproportionately large influence, leading to the observation of a random telegraph signal (RTS) when measuring conductance vs time. For example, one charge trap might be located a few Angstroms from the CNT channel, while all other traps are more distant. Random telegraph signals in CNT FETs have been studied extensively at low temperature, and two studies have reported RTS at room temperature, demonstrating that single charge sensitivity is possible in air and vacuum. , This previous work has also verified the gate-dependent capture time and emission time can be understood in a framework developed for RTS in metal-oxide-semiconductor FET devices …”
Section: Resultsmentioning
confidence: 99%
“…In small devices, such as CNT FETs, a single charge trap can have a disproportionately large influence, leading to the observation of a random telegraph signal (RTS) when measuring conductance vs time. For example, one charge trap might be located a few Angstroms from the CNT channel, while all other traps are more distant. Random telegraph signals in CNT FETs have been studied extensively at low temperature, and two studies have reported RTS at room temperature, demonstrating that single charge sensitivity is possible in air and vacuum. , This previous work has also verified the gate-dependent capture time and emission time can be understood in a framework developed for RTS in metal-oxide-semiconductor FET devices …”
Section: Resultsmentioning
confidence: 99%
“…The fabrication process of a typical CNT-FET inevitably introduces defects on the CNT, in the oxide, or at their interfaces [6], through the high-temperature annealing of SiO 2 in H 2 [7] and the interaction with high energy electrons from electron beam microscopy [8]. These defects can trap charges which may subsequently interact electrostatically with the CNT carriers.…”
mentioning
confidence: 99%
“…However, using previously determined quantum information about the measured system, the above uncertainty bound could be violated. This dramatically gives a stronger Entropic Uncertainty Relation (EUR) which has been proved recently [7,8], followed by several experimentally confirmation [9,10]. The new relation can be illustrated by the uncertainty game between two players Alice and Bob, where Bob prepares a particle in a quantum state of his choosing and sends it to Alice, who then carries out one of the two measurements and announces her choice to Bob.…”
Section: Introductionmentioning
confidence: 87%
“…On the other hand, for arbitrary duration, we demonstrate that the uncertainty change is very small, since the low acceleration approximation |k|h ≪ 1 has been imposed. Nevertheless, the range of our estimation is still under the ability of modern technology [9], therefore could serve the future experiment test.…”
Section: Uncertainty Game With Nonuniform-moving Cavitymentioning
confidence: 99%